Court services for the child in need of alternative care - Zaal, Frederick Noel (My University, 2009)
This thesis focuses on aspects of the work of South Africa's unique children's courts in care cases. Chapter 1 provides an outline of the scope of the thesis. It also explains a methodological utilisation of selected primary evaluative criteria. Throughout the thesis extensive use has been made of these to assess the sufficiency of relevant law and practice. In chapter 2 the historical origins and early impact of the children's courts are explored. It is shown that these courts have been shaped by a complex interaction between English colonial influences, progressive and liberal initiatives asserting the appropriateness of serving all children, and contrary government policies driven by racial prejudice. Chapter 3 investigates whether there is still a need for specialised care courts in a world where ADR is becoming increasingly prominent. Based upon a comparison of the respective advantages and disadvantages of courts and other resolution methodologies (including the Scottish children's hearings system) it is concluded that an interactive model involving both courts (as authoritative partners) and ADR is ideal. In chapter 4 the feasibility of encouraging direct participation at court by children and other family members is considered. It is asserted that, contrary to the situation in some systems, a direct participatory system is feasible, accords with South Africa's international obligations and for some cases is a superior method. Chapter 5 evaluates the reasons for insufficient and often inadequate legal representation of parties in the children's courts. It provides recommendations on a selection process for state subsidisation, training and what the basic functions of lawyers should be. Chapter 6 focuses on presiding magistrates. It asserts that there is an urgent need for rules of court to transform their function from an accusatorial to a predominantly inquisitorial one. It provides some discussion on the wording of these rules. It is contended that the Children's Act 38/2005, whilst expecting much more from children's court adjudicators, counterproductively diminishes specialisation and staff resources. Chapter 7 presents an argument for considerably greater and better-guided use of the children's courts to provide emergency and interlocutory relief. It proposes guidelines in the form of rules of court to enable this. Chapter 8 provides a critique of the new approach to dispositive care proceedings in the Children's Act 38/2005. It appreciates iii the significance of some valuable advances but also shows that there are fundamental structural and other deficiencies. It contains recommendations on how the Act should be both amended and supplemented by means of regulations. Chapter 9 summarises the main findings of the thesis. It is concluded that, whilst our law is still poorly developed in many important respects, the lag in systemic progress which resulted particularly during the apartheid period can now quickly be overcome. This can be done by introducing solutions proposed in the thesis which are, on the whole, financially modest. Children's courts could at last become a highly effective mechanism within our child protection system (possibly within a family court network) if these solutions are implemented.